Improving early detection of breast cancer in sub-Saharan Africa: why mammography may not be the way forward - Eleanor Black; Robyn Richmond (BMC, 2019)
Abstract Background and methods The prevention and control of breast cancer in sub-Saharan Africa (SSA) is an increasingly critical public health issue. Breast cancer is the most frequent female cancer in SSA and mortality rates from this disease are the highest globally. Breast cancer has traditionally been considered a disease of high-income countries, and programs for early detection have been developed and implemented in these settings. However, screening programs for breast cancer in SSA have been less effective than in high-income countries. This article reviews the literature on breast cancer in SSA, focusing on early detection practices. It then examines the case for and against mammography and other early detection approaches for breast cancer in SSA. Results Women with breast cancer in SSA are younger compared with high-income countries. Most women present with advanced disease and because treatment options are limited, have poor prognoses. Delay between symptom onset and healthcare seeking is common. Engagement with early detection practices such as mammography and breast examination is low and contributes to late stage at diagnosis. Discussion While early detection of breast cancer through screening has contributed to important reductions in mortality in many high-income countries, most countries in SSA have not been able to implement and sustain screening programs due to financial, logistical and sociocultural constraints. Mammography is widely used in high-income countries but has several limitations in SSA and is likely to have a higher harm-to-benefit ratio. Breast self-examination and clinical breast examination are alternative early detection methods which are more widely used by women in SSA compared with mammography, and are less resource intensive. An alternative approach to breast cancer screening programs for SSA is clinical downstaging, where the focus is on detecting breast cancer earlier in symptomatic women. Evidence demonstrates effectiveness of clinical downstaging among women presenting with late stage disease. Conclusions Approaches for early detection of breast cancer in SSA need to be context-specific. While screening programs with mammography have been effective in high-income countries, evidence suggests that other strategies might be equally important in reducing mortality from breast cancer, particularly in low-resource settings. There is a strong argument for further research into the feasability and acceptability of clinical downstaging for the control of breast cancer in SSA.